Perpetration of Violence, Violent Victimization, and Severe Mental Illness: Balancing Public Health Concerns - Choe, Jeanne Y. (2008)
OBJECTIVE: To review empirical studies, published since 1990, of the prevalence and incidence of violent perpetration and violent victimization among persons with serious mental illness and to compare their relative importance as a public health concern. METHODS: We searched three computerized bibliographic databases, MEDLINE, PSYCH INFO, and Web of Science, using the following keywords: (1) Violent perpetration: SMI, mental illness, mental disorder, psychiatric disorder, psychopathology, violence, violent behavior, and violent act(s); and (2) Violent victimization: SMI, mental illness, mental disorder, psychiatric disorder, psychopathology, and victimization. RESULTS: The search yielded 31 studies of violent perpetration and 10 studies of violent victimization. Few studies examined perpetration and victimization in the same sample. Prevalence rates varied by the type of sample and time frame (recall period). Half of the studies of violent perpetration examined inpatients; of these, about half studied only committed inpatients; these studies reported higher rates of violent perpetration (17% – 50%) compared with other samples. Among outpatients with severe mental illness, 2% to 13% had perpetrated violence in the past 6 months to 3 years, compared with 20% to 34% who had been violently victimized in the same time frame. Studies combining outpatients and inpatients reported that 12% to 22% had perpetrated violence in the past 6 to 18 months versus 35% who had been a victim of violence in the past year. CONCLUSIONS: Violent perpetration and victimization are more common among persons with severe mental illness than in the general population. Victimization is a greater public health concern than perpetration. Ironically, the discipline’s focus on the perpetration of violence among inpatients may contribute to the negative stereotypes of persons with severe mental illness.